Best bones - Nordgren, Sarah Rose (Pitt poetry series., 2014)
Winner of the 2013 Agnes Lynch Starrett Poetry Prize Best Bones is a house. When you walk around the rooms of the house, you overhear the desires and griefs of a family, as well as the unresolved concerns of lingering ghosts. The various voices in the house struggle against the family roles and social identities that they must wear like heavy garments-mother, father, wife, husband, sister, brother, servant, and master. All these voices crave unification; they want to join themselves into one whole sentient being, into "a mansion steering itself." The poems in Best Bones also explore the experience of living in a physical body, and how the natural world intersects with manmade landscapes and technologies. In it, mother has a reset button, servants blend into the furniture, and a doctor patiently oversees the pregnancy of the earth. In these poems, the body is a working machine, a repository of childhood myth and archetype, and a window to the spiritual world. The poems strive to be visceral on the level of dream, or of a story that is half remembered and half fabricated